Analisis Faktor-Faktor yang Mempengaruhi Nasabah Menggunakan Layanan Banking Mandiri - Dede Dzurotun Nisa; Tyas Silvi Ariyani; Karina Oktaviani (Jurnal Manajemen Maranatha, 2013)
Internet in e-commerce and finance have changed the businessenvironment. Customer satisfaction and customer retention increasing developed into a key success factor in e-banking. To determine these factors, this study is based on nine factors, namely Convenience, Acessilability, Future Availability, Privacy,Speed, Fees and Charges, Bank management and image, Design and Content. Data collected from bank customers who use our Internet Banking Mandiri with a sample of 100. Ninth results reveal that these factors have positive influence on the interest to use internet banking Mandiri. Factors design and content is the weakest factor to it, the bank should improve the design and content of the Bank's website in order toattract and increase customers to use Internet Banking Mandiri.Keywords: Internet banking, banking services, customer adoption